(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2012)
Introduction: TB is one of the sixth leading diseases that cause deaths in Bhutan. There were 1344 new cases in 1989 and 1060 cases in 1992. About 910 people develop tuberculosis every year. Observing the increasing trend, this study was conducted in community and in hospitals from January 2006 to June 2007 in Bhutan. The overall objective of this study is to identify the factors infl uencing delays in seeking health care for tuberculosis among TB patients and TB suspects. Methodology: The study was conducted in the community and hospital from January 2006 to June 2007 among 200 TB patients and 200 TB suspects with 5 TB patients and 5 TB suspects in depth focus group interviews with 10 groups of health workers and 10 groups of community people. Two groups of people were taken; one group had active tuberculosis and another group who were TB suspects. Moreover, health worker and community people were also asked about the disease. Two methodologies were used, one was structured questionnaires and another was in-depth and focus group interviews. Results: TB patients’ delay ranged from 0-210 days and median delay was 17.5 days. Patient’s delay in TB suspects ranged from 0 to 365 days with median delay of 14 days. “Covering mouth” while talking, was the most common stigma that came out of the interviews. Conclusion: The study brought out certain important factors like; the increasing trend of disease may be due to the fact that people delay in seeking treatment. DOI: http://dx.doi.org/10.3126/saarctb.v8i1.5890 SAARCTB 2011; 8(1): 36-40